2012
DOI: 10.1080/1097198x.2012.10845622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Culture on Knowledge Management: A Meta-Analysis and Framework

Abstract: Culture, both national and organizational, can have profound impacts on knowledge management. Yet the literature on exactly how culture impacts knowledge management is complex with no clear generalizable results. A meta-analysis was conducted on 52 articles from ten IS journals for the years 2000-2010 combining both quantitative and qualitative studies in a unique methodological approach. Key findings include a marked shift away from normative language towards more interpretive and critical discourse emphasizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 50 publications
(79 reference statements)
1
48
0
1
Order By: Relevance
“…On the other hand, a loosely controlled culture may increase an individual's contribution of their own knowledge to the achievement of organizational goals (Jarvenpaa and Staples, 2001;Wei, 2005;Alavi et al, 2005Alavi et al, -2006Jacks et al, 2012). Therefore, this leads to a reverse hypothesis of H 2b-2 to test which of the H 2b hypotheses is correct: H 2b-2 : A tightly controlled culture will have a more negative effect on the individual's knowledge storage intention than a loosely controlled culture.…”
Section: Tightly Controlled Versus Loosely Controlled Culturementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a loosely controlled culture may increase an individual's contribution of their own knowledge to the achievement of organizational goals (Jarvenpaa and Staples, 2001;Wei, 2005;Alavi et al, 2005Alavi et al, -2006Jacks et al, 2012). Therefore, this leads to a reverse hypothesis of H 2b-2 to test which of the H 2b hypotheses is correct: H 2b-2 : A tightly controlled culture will have a more negative effect on the individual's knowledge storage intention than a loosely controlled culture.…”
Section: Tightly Controlled Versus Loosely Controlled Culturementioning
confidence: 99%
“…An open system culture encourages the individual to communicate and interact with outsiders and newcomers (Gupta et al, 2000;Wei, 2005;Jacks et al, 2012). As the most difficult part of knowledge transfer is the transfer of tacit knowledge, the sharing of such knowledge must be done through continuous openness, trust, common language, and tacit agreement (Norman, 2004;Ajmal and Koskinen, 2008).…”
Section: Closed System Versus Open System Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This view treats knowledge as an asset (a resource) and as an object that can be extracted from an individual's mind and stored externally to be used by others, like any other object. A review by Jacks et al (2012) suggests that the literature has moved from an essentially normative approach to more interpretive and critical views of knowledge over the 10-year period between 2000 and 2010, although there is still considerable research that remains wedded to the resource view of knowledge, even if this is only implicit.…”
Section: S Newellmentioning
confidence: 96%
“…Some studies have also looked at the impact of national culture. Thus, a metaanalysis on the impact of culture, both national and organizational, on KM, covering the period 2000-2010 (Jacks et al, 2012) revealed that most research has focused on organizational rather than national culture. In terms of national culture, this meta-analysis revealed that those studies that have been undertaken identify the importance of uncertainty avoidance and power distance (Hofstede, 1980) as having most influence on knowledge sharing; while at the organizational level, trust and openness are most important, with these influencing knowledge sharing directly but also indirectly through business leadership's vision and strategy.…”
Section: What Do We Mean By Knowledge?mentioning
confidence: 99%